Disordered eating among preadolescents boys and girls: the influence of children´s and mother's variables - Gonçalves, Sónia (2012)
It is well recognized that behaviors and attitudes, such as restrained eating, fear of fat, distortion of body image, binge eating, and purging are very common among preadolescents from both sexes. However, few studies have evaluated the role of some personnel and mother’s variables in the prediction of eating problems separately from children’ sexes. Thus, this study was two main goals. The first one was analyzing eating behaviors and body satisfaction on boys and girls and also analyzing their mothers’ perceptions on these two domains. The second one was to evaluate the predictors of eating problems using some children variables (BMI, self-worth, and body satisfaction) and some mother’s variables (BMI, eating problems, and mother’s satisfaction with the body of their child). In total, 111 children and respective mothers participated in this study. Children (54.1% girls) were between 9 to 12 years old (M = 10.08; SD = 0.81) and mothers were between 27 to 60 years old (M = 39.58; SD = 5.27). Children were asked to complete the Children’s Eating Attitude Test, and the Self-Perception Profile for Children. Mothers were asked to complete the Eating Disorders Examination Questionnaire, and the Child Eating Behavior Questionnaire. Children’s and mother’s measures also include body mass index (BMI), and Collins Figure Drawings. The Results showed that: i) no association was found between children´s BMI and mother’s BMI for both sexes; ii) no differences were found between boys and girls on eating behavior; iii) most of the children revealed that they would like to have a body image distinct from the one they have; iv) likewise, most of the mothers referred the desire of a thinner body image for their children; v) greater BMI was related to higher body dissatisfaction on both sexes vi) the child's BMI and dissatisfaction with body image were predictors of eating disturbance in boys, and the self-worth, mother’s BMI, and eating behavior were predictors of girls eating disturbance. In conclusion, these findings suggest that maternal influences on child eating disturbance differ according to child sex. Mother’s eating problems and BMI was related to girls eating problems, but no maternal influences were found for boys.